Squarespace 6 for dummies - Black, Kris (For dummies, 2013)
Build your own blog, website, or portfolio with Squarespace Squarespace lets you create visually rich web pages with any configuration of text, images, or blocks you wish, just by dragging and dropping. Even if you've been using earlier versions of Squarespace, the features in version 6 will amaze you - and bring you straight to this must-have guide for practical information! If you're a do-it-yourself website builder, get up to speed fast on all the next-generation Squarespace tools, including cool new features for mobile sites, SEO, social networks, and more. Brings you u.